Fabrication of the SnS2/ZnIn2S4 heterojunction for highly efficient visible light photocatalytic H2 evolution. (12th March 2022) - Geng, Yanling; Zou, Xiaoli; Lu, Yanan; Wang, Lei
Abstract: A series of SnS2 /ZnIn2 S4 ( x -SS/ZIS) photocatalysts with different mass ratios of SnS2 were prepared by a hydrothermal method. The resulted composites were used for photocatalytic hydrogen evolution under visible light excitation. All the SS/ZIS composites exhibited significantly enhanced photocatalytic activity for H2 evolution. Obviously, the highest H2 evolution rate of 769 μmol g −1  h −1 was observed over 2.5-SS/ZIS, which was approximately 10.5 times that of the ZnIn2 S4 (73 μmol g −1  h −1 ). The enhanced photocatalytic performance was attributed to the successful construction of SnS2 /ZnIn2 S4 heterojunctions, leading to rapid charge separation and fast transfer of the photo-generated electrons and holes under light irradiation. On the basis of PL, electrochemical impedance spectroscopy (EIS), photocurrent measurements and the H2 evolution tests, a plausible photocatalytic mechanism was proposed. Highlights: SnS2 /ZnIn2 S4 composites were synthesized from SnS2 nanosheets and ZnIn2 S4 microspheres. SnS2 /ZnIn2 S4 heterojunctions enhanced photocatalytic H2 production under visible light. Efficient charge separation and transfer at the heterojunctions explained the improved performance.